PENGARUH PENERAPAN MODEL PEMBELAJARAN OSBORN TERHADAP HASIL BELAJAR SISWA SMP KELAS VIII - Adiputera N. Lontoh; John R. Wenas; Marvel G. Maukar (ADIBA : JOURNAL OF EDUCATION, 2022)
Education is very important to increase the potential and abilities of each person, so that they are able to face developments and changes that occur. Mathematics education is given with the aim that students can adapt to the rapid development of the world. Through the right learning model will produce good learning outcomes. This study aims to determine the learning outcomes taught with the Osborn learning model are higher than those using the conventional learning model with the lecture method. This research uses a quantitative approach with a quasi-experimental type of research. The data analysis method used is descriptive analysis, normality test, and Mann Whitney test which is processed using the SPSS (Statistical Product and Service Solutions) program. The results of this study show that student learning outcomes using the Osborn learning model are higher than those using the conventional model.